The correlation of cardiovascular risk factors and angiographic findings with serum vitamin D levels in patients undergoing coronary angiography - S. K., Tripathy; N., Dhal; S., Pattnaik; S. N., Routray; S., Das; S. K., Mishra; M., Panigrahi; B., Mohanty; M. R., Behera (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Studies regarding correlation of various conventional risks factors for Coronary Artery Disease (CAD) are many. Keeping in mind the scarcity of studies regarding Vit-D Deficiency (VDD), a new risk factor in CAD, present study was conducted to correlate Vit-D level with conventional risk factors and Coronary Angiography (CAG). Methods: Hundred adult patients admitted to Medicine and Cardiology undergoing CAG with suspected or established CAD were kept in study. Patients having renal, hepatic, parathyroid disease, osteomalacia and patients taking drugs interfering with Vitamin D (Vit-D) metabolism were excluded. After detailed history and thorough clinical examination, routine investigations and 25-(OH) D level was estimated. Subsequently patients underwent CAG. Statistical analysis by Mann Whitey test and Chi-square Test was done and inference was drawn. Results: 100 patients in different age groups had hypertension (HTN) in 53, diabetics mellitus (DM) 39, dyslipidemia 62, smokers 38 and family history of CAD 19. CAG showed normal coronaries in 4, Single Vessel Disease (SVD) in 30, double vessel diseases (DVD) 43 and triple vessel disease (TVD) 22. Vit-D level <20ng/ml i.e. Vit-D deficiency (VDD) in 68, 20-30ng/ml i.e. Vit-D insufficiency (VDI) in 22 and >30ng/ml (normal) in 10. VDD was profound in 51-60 and 61-70 years age groups. Statistical correlation of VDD was not significant with conventional risk factors, but statistically significant correlation of VDD was observed with dyslipidemia and CAG findings in our study. Conclusions: Like earlier studies we observed significant correlation of Vit-D levels with CAD. Though dyslipidemia was significantly correlated with VDD, correlation of other conventional risk factors like age, sex, HTN, DM, smoking and family history was not found. We conclude from this study presence of significant association of VDD with severe CAD. DVD and TVD by CAG were common with low Vit-D levels.